2018
DOI: 10.1186/s12906-018-2289-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of Phyllanthus amarus Schum. & Thonn. through inhibition of NF-κB, MAPK, and PI3K-Akt signaling pathways in LPS-induced human macrophages

Abstract: BackgroundPhyllanthus amarus has been used widely in various traditional medicines to treat swelling, sores, jaundice, inflammatory diseases, kidney disorders, diabetes and viral hepatitis, while its pharmacological and biochemical mechanisms underlying its anti-inflammatory properties have not been well investigated. The present study was carried out to investigate the effects of 80% ethanolic extract of P. amarus on pro-inflammatory mediators release in nuclear factor-kappa B (NF-кB), mitogen activated prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 46 publications
5
65
0
2
Order By: Relevance
“…After the treatment, the cells were further incubated for 4 hr with 10% of Alamar blue reagents. Finally, the reduction of resazurin into resorufin by viable cells was read with microplate reader (Tecan Trading AG, Switzerland) at 570 nm (Harikrishnan, Jantan, Haque, & Kumolosasi, ).…”
Section: Methodsmentioning
confidence: 99%
“…After the treatment, the cells were further incubated for 4 hr with 10% of Alamar blue reagents. Finally, the reduction of resazurin into resorufin by viable cells was read with microplate reader (Tecan Trading AG, Switzerland) at 570 nm (Harikrishnan, Jantan, Haque, & Kumolosasi, ).…”
Section: Methodsmentioning
confidence: 99%
“…The MyD88-dependent signalling pathway activated NF-κB to induce the inflammatory cytokine TNF-α [ 39 ]. Recent reports have shown that traditional Chinese medicines have therapeutic potential in inflammatory response and GDM [ 40 43 ]. Taking into account the inflammatory response involved in GDM [ 29 , 44 ], we evaluated the effects of puerarin treatment on IRS-1, TLR4, MyD88, and NF-κB expression in GDM rats.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that phosphorylated IB and p-65 protein expression levels were markedly increased in cigarette-smoke-induced lung inflammation GLRX1 knockout mice (31). In addition, several studies have reported that the phosphorylated NF-B and MAPKs expression levels were increased in LPS-treated macrophages (39)(40)(41). In contrast, overexpression of GLRX1 decreased S-glutathionylation IKK Cys179 and increased NF-B activation after oxidation induced by oxidative stress, suggesting that cellular content of GLRX1 regulates the activation of NF-B under oxidative stress (42).…”
Section: Effect Of Pep-1-glrx1 On the Nf-b And Mapk Signaling Pathwaysmentioning
confidence: 99%